Spatial econometric models for crime control in Peru: a real-time optimization approach - Caparó, Rafael (2017)
The degree of spatial correlation between the regions shows that there is a contagion effect at the crime level, especially in the peripheral regions of Lima. A positive relationship has been found that progresses from region to region, from district to district, with positive trends and clear dependencies with income levels and population density, especially in the districts located in the cones, confirming that the model can contrast reality and predict future scenarios in terms of crime levels. Although the technology related to information storage is limited, we present an alternative for data collection and some codes for storing large volumes of data, especially those related to the georeferenced positions of high crime areas, which have served to find patterns of regional expansion of criminal acts, monitor them and propose alternatives for improvement.